The Effect of Gamma Irradiation on the Optical Constants of (HDPE-PP) Blends - Hasan, B.; H., Ahmad; Hasan, S. (Iraqi Journal of Science, 2025)
The influence of gamma radiation and blend ratio on the optical constants (refractive index (n), extinction coefficient (k), and real & imaginary parts of dielectric constants (C) & (C)) for high density polyethylene (HDPE) Polypropylene (PP) blends using the transmittance and reflectance spectra have been discussed. For unirradiated samples the results showed that (n) increases in rich PP sample while (k) declared strong dependence on blends ratio and revealed systematie variation. It was found that (n) increases as a result of irradiation by gamma-ray with doses (80 and 240) kGy indicating that polymer chain crosslinking is the dominate phenomena, while for irradiation with dose 160 kGy (n) is found to decrease indicating that polymer degradation is the dominate phenomena (chain scission).